Complete chloroplast genome data reveal the existence of the Solidago canadensis L. complex and its potential introduction pathways into China - Yu-Tian Tao; Yu-Tian Tao; Lu-Xi Chen; Ming Jiang; Jie Jin; Zhong-Shuai Sun; Chao-Nan Cai; Chao-Nan Cai; Han-Yang Lin; Han-Yang Lin; Allison Kwok; Jun-Min Li; et al. (Frontiers in Plant Science)
Solidago canadensis, native to North America, is an invasive species in many areas of the world, where it causes serious damage to natural ecosystems and economic losses. However, a dearth of genetic resources and molecular markers has hampered our understanding of its invasion history. Here, we de novo assembled 40 complete chloroplast genomes of Solidago species, including 21 S. canadensis individuals, 15 S. altissima individuals, and four S. decurrens individuals, the sizes of which ranged from 152,412 bp to 153,170 bp. The phylogenetic trees based on the complete chloroplast genome sequences and nuclear genome-wide SNP data showed that S. canadensis and S. altissima cluster together and form a monophyletic pair, as sister to S. decurrens, indicating the existence of the S. canadensis L. complex in China. Three potential introduction pathways were identified. The chloroplast-genome structure and gene contents are conservative in the genomes of the S. canadensis L. complex and S. decurrens. The analysis of sequence divergence indicated five variable regions, and 10 chloroplast protein-coding genes that underwent positive selection were identified. Our findings shed new light on the invasion history of S. canadensis and the data sets generated in this study will facilitate future research on its chloroplast genome evolution.